(untitled) (Research, Society and Development, 2021)
Sausages are widely accepted by the population, as they have low cost and practical preparation. However, in general, they have a low content of important dietary fibers that prevent chronic non-communicable diseases. Barley is a grain highly produced in Brazil for beer production, which leads to the generation of a large amount of brewery waste (BW), called barley malt bagasse, intended for animal feed or discarded in the environment. The objective of this research was to produce a sausage with the incorporation of barley malt bagasse flour (BMBF) and evaluate it. Five sausage formulations were produced: 0%, without incorporating barley malt bagasse flour (BMBF); and the others according to the percentage of flour incorporation in substitution to textured soy protein, with 0.5%, 1%, 2% and 4%. The experiment was conducted in a randomized block design and the results were subjected to analysis of variance, followed by adjustment of regression models, at 5% significance. This research allowed the preparation of a “sausage type” product with the incorporation of BMBF, which has a higher amount of crude fiber, crude protein, firmness and a lower percentage of ether extract in relation to the control sausage. It was found that the amount of ash decreased and the water activity did not change significantly with the incorporation of BMBF. As for microbiological parameters, sausages met the requirements of the current legislation. Additional studies would be interesting to assess the sensory characteristics of the product developed and its production potential at the industrial level.